A typology and meta-analysis of outsourcing relationship frameworks. Issue 2 (10th June 2014) - Lyons, Paul; Brennan, Louis
Abstract : Purpose: – The purpose of this paper was to consider 52 conceptual frameworks identified during a systematic literature review with the aim of providing insights into various aspects of outsourcing relationships. Many authors propose these frameworks to contribute to our understanding of how outsourcing relationships are conceived, operate and evolve. A meta-analysis of these frameworks was completed. Design/methodology/approach: – The approach consisted of five stages: a systematic, but focused literature review to identify relevant frameworks; a study of the selected frameworks to enable the design of a typology of framework styles, so that frameworks adopting similar styles can be compared and analysed; grouping of the frameworks into families addressing different aspects of relationships as they form, operate and evolve; using the types (from the typology) within these family groups to facilitate a meta-analysis of each group by identifying common or contrasting themes; and deriving overall observations and identifying the most robust frameworks in each group. Findings: – Nine framework types are identified and named as nominal categorisation, matrix, pyramid, dependency, interaction, flowchart, two-dimensional progression, life cycle and stepped. Five logical family groups were identified addressing how relationships form, operate and evolve. These groups cover the scope of outsourcing relationship, the relationship governance, the climate of the relationship, relationship tactics and relationship evolution. Common themes were identified, and overall observations were drawn. Recommendations are also provided on the frameworks which were assessed as being most robust and likely to be of most use to practitioners and researchers. Research limitations/implications: – The study considered a representative sample of frameworks identified during a systematic review of literature relating to outsourcing relationships. However, it cannot be considered fully comprehensive, and frameworks from other sources also exist. Practical implications: – Outsourcing success depends on the establishment and management of a constructive relationship between the client and supplier. Frameworks assist understanding of this important aspect of outsourcing. Originality/value: – This paper provides a reference point for scholars and practitioners who are interested in outsourcing relationships and may value the sources identified and the summaries, comparisons and recommendations provided.